Comparative Plastid Genomics of Cryptomonas Species Reveals Fine-Scale Genomic Responses to Loss of Photosynthesis. (10th January 2020) - Tanifuji, Goro; Kamikawa, Ryoma; Moore, Christa E; Mills, Tyler; Onodera, Naoko T; Kashiyama, Yuichiro; Archibald, John M; Inagaki, Yuji; Hashimoto, Tetsuo
Abstract: Loss of photosynthesis is a recurring theme in eukaryotic evolution. In organisms that have lost the ability to photosynthesize, nonphotosynthetic plastids are retained because they play essential roles in processes other than photosynthesis. The unicellular algal genus Cryptomonas contains both photosynthetic and nonphotosynthetic members, the latter having lost the ability to photosynthesize on at least three separate occasions. To elucidate the evolutionary processes underlying the loss of photosynthesis, we sequenced the plastid genomes of two nonphotosynthetic strains, Cryptomonas sp. CCAC1634B and SAG977-2f, as well as the genome of the phototroph Cryptomonas curvata CCAP979/52. These three genome sequences were compared with the previously sequenced plastid genome of the nonphotosynthetic species Cryptomonas paramecium CCAP977/2a as well as photosynthetic members of the Cryptomonadales, including C. curvata FBCC300012D. Intraspecies comparison between the two C. curvata strains showed that although their genome structures are stable, the substitution rates of their genes are relatively high. Although most photosynthesis-related genes, such as the psa and psb gene families, were found to have disappeared from the nonphotosynthetic strains, at least ten pseudogenes are retained in SAG977-2f. Although gene order is roughly shared among the plastid genomes of photosynthetic Cryptomonadales, genome rearrangements are seen more frequently in the smaller genomes of the nonphotosynthetic strains. Intriguingly, the light-independent protochlorophyllide reductase comprising chlB, L, and N is retained in nonphotosynthetic SAG977-2f and CCAC1634B. On the other hand, whereas CCAP977/2a retains ribulose-1, 5-bisphosphate carboxylase/oxygenase-related genes, including rbcL, rbcS, and cbbX, the plastid genomes of the other two nonphotosynthetic strains have lost the ribulose-1, 5-bisphosphate carboxylase/oxygenase protein-coding genes.